Tocilizumab Employment in the Treatment of Resistant Juvenile Idiopathic Arthritis Associated Uveitis. (2nd January 2021) - Maleki, Arash; Manhapra, Ambika; Asgari, Soheila; Chang, Peter Y.; Foster, C. Stephen; Anesi, Stephen D.
ABSTRACT: Aim: To determine the efficacy and safety of intravenous tocilizumab in refractory juvenile idiopathic arthritis associated uveitis. Patients and Methods: This was a retrospective observational case series. Patients with refractory juvenile idiopathic arthritis associated uveitis, who had received tocilizumab were included in this study. Results: 8 patients (14 eyes) were included in this study. The average age of the patients at the first visit was 16.8 ± 11.2 years (7–40). The average duration of follow-up period after starting treatment was 28.6 ± 24.6 months (9–70). Intravenous tocilizumab infusions induced and maintained remission in 5 patients (8 eyes). Vasculitis was resolved within 8 months in all but one patient. The presence of papillitis before starting treatment was directly correlated with visual acuity improvement. No side effects were observed. Conclusion: Intravenous tocilizumab infusion can be an effective and safe method of treatment to induce and maintain remission in resistant juvenile idiopathic arthritis associated uveitis.